Determinants of sleep disturbance and sleep quality in children of mothers with fibromyalgia - Işıl Fazilet Kartaloğlu; Sevil Karagül; Şule Arslan (Archives of Rheumatology, 2023)
Objectives: This study aimed to determine whether maternal diagnosis of Fibromyalgia syndrome (FMS) affects the sleep quality of children. Patients and methods: This prospective study was conducted with 80 female participants (mean age: 36.2±5.9 years; range 25 to 50 years) and their 80 children (27 males, 53 females; mean age: 6.6±2.6 years; range 2 to 12 years) between August 2019 and November 2020. The FMS group included 40 female FMS patients and their children, whereas the control group consisted of 40 healthy females and their children. In addition to sociodemographic variables, functional status was evaluated by the Fibromyalgia Impact Questionnaire (FIQ), which was completed by mothers with FMS, and the Children’s Sleep Habits Questionnaire (CSHQ) was used to evaluate the sleep quality of all children. Results: There was no statistically significant difference between the two groups in terms of demographic characteristics (p>0.05). The CSHQ score of the two groups was above 41 points and was at a clinically significant level. The median value for the CSHQ score was 60.5 and 52 in the FMS and control groups, respectively. Sleep time, waking up at night, parasomnias, disrupted breathing during sleep, and sleepiness scores were higher in the FMS group than in the control group, and the differences were statistically significant (p<0.001). The delayed falling asleep score, which was reversely coded, was lower in the FMS group than in the control group, and the difference was statistically significant (p<0.001). Conclusion: This pilot study showed that the children of mothers with high Fibromyalgia Impact Questionnaire scores had sleep disorders. Maternal diagnosis of FMS negatively affects the sleep quality of children.